The Influence of Change Management, IT Infrastructure Capability, and Knowledge Management on Digital Transformation Success in Healthcare Units - Tawil, Muhamad Risal; Hendratni, Tyahya Whisnu; Hamdany, Mohammad Azharie; Salim, Brian Sebastian; Akhirianto, Pas Mahyu; Dorothy, Natasha Auriel (Journal of Information System, Technology and Engineering, 2025)
The​‍​‌‍​‍‌ research reviewed the influence of change management, IT infrastructure, and knowledge management on the health units sector in Indonesia. A quantitative, explanatory research design along with a survey research method was employed to carry out this study, where data were obtained from a sample of 180 staff and managers in hospitals, community health centres and clinics with integrated digitised health systems. Some of the respondents were chosen through purposive sampling, mainly those who were directly involved in the digitisation process in the health sector. In the end, the three variables were all found to have positively and significantly influenced the success of the digital transformation. Hence, the success of digital transformation depends on the effective management of change, the quality of the infrastructure, and the organization's knowledge stock and flow the capability to capture, process, and disseminate ​‍​‌‍​‍‌knowledge.